THE ROLE OF TASKS IN THE DEVELOPMENT OF MATHEMATICAL LITERACY OF PRIMARY CLASS STUDENTS (Spectrum Journal of Innovation, Reforms and Development, 2023)
In the organization of mathematics classes, it is necessary to pay more attention to imparting knowledge in a practical way rather than theoretical knowledge and to some extent abandon the approach based on providing students with ready-made educational materials. In mathematics lessons, it is recommended to use modern interactive methods suitable for the topic that is interesting for more students.